First hollow stem: a critical wheat growth stage for dual‐purpose producers. Issue 1 (5th February 2016) - Edwards, Jeff; Horn, Gerald
Abstract : The purpose of this article is to explain why first hollow stem (FHS) is the best time to remove cattle from wheat pasture, provide details on how to identify FHS, and discuss some of the environmental and physiological factors that determine when FHS occurs. Earn 0.5 CEUs in Crop Management by reading this article and completing the quiz at www.certifiedcropadviser.org/certifications/self‐study/752 .